Implementing the “Wisdom of the Crowd” - Kremer, Ilan; Mansour, Yishay; Perry, Motty (Journal of Political Economy, 2014)
We study a novel mechanism design model in which agents each arrive sequentially and choose one action from a set of actions with unknown rewards. The information revealed by the principal affects the incentives of the agents to explore and generate new information. We characterize the optimal disclosure policy of a planner whose goal is to maximize social welfare. One interpretation of our result is the implementation of what is known as the “wisdom of the crowd.” This topic has become increasingly relevant with the rapid spread of the Internet over the past decade.